Resource-based cities: Spatial structure and evolutionary identification based on nighttime light images - Lu, Shuo; Zhang, Wenzhong; Li, Jiaming; Wang, Shaohua (Frontiers in Earth Science, 2022)
Dividing the development stage and grasping the best time to transition is significant for resource-based cities (RBCs). However, there is still a lack of research on how to judge the developmental stage of RBCs through objective indicators of urban development. However, identifying the developmental stage of RBCs relies heavily on the researcher's subjective judgment. Based on nighttime light data, this study utilizes the urban center primacy ratio as a unique indication of the growth stage of RBCs. This method is more detailed and objective than studies that define stages of development based on socio-economic indicators. It provides a fresh viewpoint on the stages of urban life cycle development. Based on the mining economy's development cycle, the proportion of mining employees at 3.9 percent and 44.9 percent can be used to divide RBCs into growth, maturity, recession, and regeneration periods, with 3.9 percent serving as the dividing line between RBCs and non-RBCs. In addition, when an RBC reaches maturity, a particular range of the urban center primacy ratio has a positive correlation with the GDP growth rate and negatively correlated outside of that range. This indicates that this phase is crucial for the shift from agglomeration diseconomy to agglomeration economy. The government and social institutions can use this period to drive the economic transformation of RBCs through various policies and actions.